Structure and NO2 gas sensing properties of SnO2-core/In2O3-shell nanobelts - Kim, Hyunsu; An, Soyeon; Jin, Changhyun; Lee, Chongmu (Current applied physics, 2012)
SnO2-core/In2O3-shell nanobelts were fabricated by a two-step process comprising thermal evaporation of Sn powders and sputter-deposition of In2O3. Transmission electron microscopy and X-ray diffraction analyses revealed that the core of a typical core–shell nanobelt comprised a simple tetragonal-structured single crystal SnO2 and that the shell comprised an amorphous In2O3. Multiple networked SnO2-core/In2O3-shell nanobelt sensors showed the response of 5.35% at a NO2 concentration of 10 ppm at 300 °C. This response value is more than three times larger than that of bare-SnO2 nanobelt sensors at the same NO2 concentration. The enhancement in the sensitivity of SnO2 nanobelts to NO2 gas by sheathing the nanobelts with In2O3 can be accounted for by the modulation of electron transport by the In2O3–In2O3 homojunction. ► SnO2-core/In2O3-shell nanobelts were fabricated by a two-step process. ► The core–shell nanobelt sensors showed the response of 5.35% at NO2 10 ppm. ► This response value is more than 3 times larger than that of SnO2 nanobelts. ► The enhancement is due to the In2O3–In2O3 homojunction.